NEUROMARKETING IN THE POSITIONING OF A BRAND OF MINERAL WATER FOR HUMAN CONSUMPTION - Olivera Olivera, Angel Augusto (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
In Venezuela, neuroscience is beginning to be included in marketing. That is observed in advertising campaigns and market studies. But, it is publicly unknown what techniques are being used or how they are being applied. This article has described a methodology to apply neuromarketing to studies and research in the marketing of goods, products and services. In this case, we will present the application of neuromarketing to the positioning of water in bottles for human consumption. The ZMET technique designed for metaconscious exploration experiments was applied, which was complemented by a market study based on ethnographic observation. The results obtained were satisfactory for experimentation and for subsequent implementation. To date, we have concluded that the basis of the study is in the formation of a team of multidisciplinary professionals, continue experimenting and then move on to a second phase with the incorporation of body exploration techniques, including equipment, instruments, systems and operator personnel. We have perceived that neuromarketing is beyond including emotions in the purchase decision. Neuromarketing, rather, is to harness the full potential of the human brain in thoughts, decisions and actions related to value propositions for people.